Surgical manifestations and management of gastrointestinal and hepato-pancreato-biliary ascariasis: an observational study - Anand, Madhur; Topno, Noor; Hajong, Ranendra; Baruah, Arup J.; Khongwar, Donkupar; Agarwal, Swati (International Surgery Journal, 2020)
Background: Ascaris lumbricoides is the largest intestinal nematode parasite of humans. This study describes different presentations and management patterns of gastrointestinal and hepato-pancreato-biliary ascariasis presenting to a tertiary centre of North-eastern India. Methods: This was a prospective observational study aimed to study the presentations and management patterns of Ascaris related surgical diseases including intestinal obstruction, pancreatitis and cholangitis in a tertiary centre of Northeast India. All consenting cases of gastrointestinal and hepato-pancreato- biliary ascariasis admitted in our hospital were included. Results: Ninty patients with Ascaris sequeale were included, which included biliary ascariasis without cholangitis: 36, pancreatitis: 30, cholangitis: 18 and sub-acute intestinal obstruction: 6. Ultrasound was the most useful diagnostic investigation followed by stool examination and endoscopy. Hepato-pancreato-biliary ascariasis was managed conservatively and the progress monitored with sonography. The surgical management choledocho-duodenostomy was done for three patients having biliary ascariasis with unresolving obstructive jaundice and recurrent cholangitis on conservative management and 6 patients underwent therapeutic endoscopic worm removal. There were no deaths. No patient needed ICU care. Conclusions: Sonography can be helpful in diagnosing the presence of worms, its complications and in evaluating response to treatment. Hepato-pancreato-biliary ascariasis can be managed conservatively for majority of the patients.